Karima Moyer-Nocchi: Chewing the Fat, an oral history of Italian foodways from Fascism to Dolce Vita - Riley, Gillian (Petits Propos Culinaires, 2016)
Karima Moyer-Nocchi: Chewing the Fat, an oral history of Italian foodways from Fascism to Dolce Vita: Medea Publishing, 2015: 428 pp., paperback, £14.00.